Efeito de um primer experimental contendo carbodiimida na atividade de metaloproteinases, degradação do colágeno e da união resina-dentina - Delgado, Cláudia Cristina [UNESP] (2015)
Objective: To evaluate the effect of an experimental primer containing EDC on the total matrix metalloproteinases (MMPs) activity, collagen degradation and resin-dentin bond stability. Methods: Two studies were developed to answer to the objectives of this dissertation. Study 1: One hundred dentin beams (1x1x6 mm) were obtained from sound human permanent molars. Fifty specimens were acid-etched with 37% phosphoric acid and treated for 60s with (n=10): deionized water (control), 0.5 mol/L EDC, experimental primer (EP), experimental primer with 0.5 mol/L EDC (EP+EDC) or Scotchbond MP primer (SBMP). After rinsing, the total MMP activity was assessed by a colorimetric assay (SenSolyte). Additionally, 20 specimens were subjected to a caries-inducing protocol. These and the remaining 20 sound specimens were completely demineralized in 10% phosphoric acid for 18h. The specimens were treated as mentioned above and stored in saliva-like solution for 15 days at 37°C. After this period, the saliva was collected for the quantification of hydroxyproline (HYP) release. MMP activity and HYP release were submitted to ANOVA and Tukey tests (p<0.05). Study 2: Flat dentin surfaces were obtained from 32 sound third molars. The dentin was acid-etched for 15s and treated (n=8) as described in the study 1, except for deionized water. After treatment, the bond of SBMP was applied to all teeth and resin blocks were constructed. After 24h, the teeth were cut into specimens with 0.81 mm2 of cross-sectional area, which were stored in saliva-like solution for 24h or 6 mo prior to microtensile testing. The bond strength values (MPa) were submitted to two-way ANOVA, Tukey and chi-square (χ2) tests (p<0.05). Types of fractures were descriptively analyzed. Results: All treatments reduced the activity of MMPs, however, 0.5 mol/L EDC (92%) and the EP+EDC (78%) were the most effective...(Complete abstract electronic access below)